The fatal outcome of a child with a delayed posterior urethral valve diagnosis in a low income country: a case report and take home messages - M. Metogo, Jacqueline Ze Minkande, Francky Teddy A. Endomba, Jan RenÃƒÂ© Nkeck, Joel Noutakdie Tochi (Journal of Medical Biomedical and Applied Sciences, 2017)
Introduction: When faced with early urinary tract infections in infants, there is a need to do diagnostic imaging to exclude urinary tract malformations. Delayed diagnosis of this condition could lead to serious complications.Case presentation: We received a 2 months old male infant referred for better management of an acute kidney injury (AKI) with septicemia. He had a past medical history of febrile urinary tract infection. Our diagnosis was that of acute kidney injury and septicemia associated to a posterior urethral valve. The initial treatment included broad spectrum antibiotics, management of AKI complications and vesicostomy to relief the urinary obstruction prior to valve ablation. We unfortunately lost the infant on day 3 following surgery from severe refractory hyperkaliemia and a uremic syndrome.Conclusion: This case is a call to cliniciansâ attention in low income countries to always check for urinary tract malformations when confronted with an infant presenting a febrile urinary tract infection.Key-words: Acute kidney injury, child, diagnosis delay, posterior urethral valve, Cameroon.